2005
DOI: 10.1016/j.rapm.2005.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Analysis of Bipolar Radiofrequency Lesions: Implications for Treatment of the Sacroiliac Joint

Abstract: Bipolar radiofrequency treatment creates continuous "strip" lesions proportional in size to the distance between the probes when the distance between cannulae is 6 mm or less. Spacing the cannulae 4 to 6 mm apart and treating at 90 degrees C for 120 to 150 seconds maximizes the surface area of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 11 publications
(9 reference statements)
2
53
2
1
Order By: Relevance
“…[19] Similarly, Pino et al noted that bipolar RF created the largest lesion in performing thermocoagulation at 90 o C for 120-150 seconds with 4-6 mm intervals of two electrodes. [21] Derby and Lee reported that bipolar electrodes produce greater thermocoagulation and better coagulation on a larger area than that of monopolar electrodes. [22] In our study, radiofrequency lesioning was created at a temperature of 80°C for 120 seconds in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Similarly, Pino et al noted that bipolar RF created the largest lesion in performing thermocoagulation at 90 o C for 120-150 seconds with 4-6 mm intervals of two electrodes. [21] Derby and Lee reported that bipolar electrodes produce greater thermocoagulation and better coagulation on a larger area than that of monopolar electrodes. [22] In our study, radiofrequency lesioning was created at a temperature of 80°C for 120 seconds in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have studied the morphology of bipolar lesions using various mediums, from animal tissue to egg white. Pino et al examined bipolar RF lesion patterns in egg white by heating 22-gauge electrodes in parallel [109]. They reported that the optimum contiguous 'strip' lesion occurred when the electrodes were placed 6 mm apart.…”
Section: Bipolar Rfmentioning
confidence: 99%
“…5 Compared with conventional monopolar-RF, bipolar-RF has been shown to increase lesion size as a function of parameters such as lesioning time, temperature, fluid injection, and electrode active tip site and spacing. [5][6][7][8] Alternatively, cooled-RF was also developed to increase lesion size. It involves an electrode in which the tip is water-cooled for the duration of the lesion.…”
mentioning
confidence: 99%